A comparative analysis of energy expenditure and substrate metabolism in male university students with overweight/obesity: Tabata vs HIIT and MICT - Wang, Yongbo; Fan, Changming; Cheng, Lin; Wang, Yifei; Peng, Danxing; Li, Fengcai; Han, Yanbai; Wang, Hongli (Frontiers in Endocrinology, 2024)
Introduction:Exploring the energy expenditure and substrate metabolism data during exercise, 10minute recovery, and 20-minute recovery phases in Tabata, HIIT(High-Intensity Interval Training), and MICT(Moderate-Intensity Continuous Training). This study explores the scientific aspects of weight reduction strategies, examining energy expenditure and substrate metabolism from various training perspectives. The aim is to establish a theoretical foundation for tailoring targeted exercise plans for individuals within the population with overweight/obesity.Methods:This study used an experimental design with fifteen male university students with overweight/obesity. Participants underwent random testing with Tabata, HIIT, and MICT. Tabata involved eight sets of 20 seconds exercise and 10 seconds rest, totaling 4 minutes. HIIT included four sets of power cycling: 3 minutes at 80% VO2max intensity followed by 2 minutes at 20% VO2max.MICT comprised 30 minutes of exercise at 50% VO2max intensity. Gas metabolism indices were continuously measured. Subsequently, fat and glucose oxidation rates, along with energy expenditure, were calculated for each exercise type.Results:During both the exercise and recovery phases, the Tabata group exhibited a significantly higher fat oxidation rate of 0.27 ± 0.03 g/min compared to the HIIT group (0.20±0.04 g/min, p＜0.05) and the MICT group (0.20±0.03g/min, p＜0.001). No significant difference was observed between the HIIT and MICT groups (p=0.663).In terms of energy expenditure rate, the Tabata group maintained a substantially elevated level at 5.76±0.74kcal/min compared to the HIIT group (4.81±0.25kcal/min, p＜0.01) and the MICT group (3.45±0.25kcal/min, p＜0.001). Additionally, the energy expenditure rate of the HIIT group surpassed that of the MICT group significantly (p＜0.001).Conclusions:The study finds that male college students with overweight/obesity in both exercise and recovery, Tabata group has lower fat and glucose oxidation rates, and energy expenditure compared to HIIT and MICT groups. However, over the entire process, Tabata still exhibits significantly higher rates in these aspects than HIIT and MICT. Despite a shorter exercise duration, Tabata shows a noticeable "time-efficiency" advantage. Tabata can be used as an efficient short-term weight loss exercise program for male college students with overweight/obesity.